EKSPERIMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING, GROUP INVESTIGATION DAN THINK PAIR SHARE DENGAN PENDEKATAN SAINTIFIK DITINJAU DARI KEMAMPUAN PENALARAN SISWA - Ardani, Anwar; Budiyono, Budiyono; Subanti, Sri (Jurnal Pembelajaran Matematika, 2015)
Abstract: The aim of this research was to find out the different effect of learning models using scientific approach on the studentsâ learning achievement viewed from the studentsâ reasoning ability. This study was a quasi-experimental research with a 3x3 factorial design. The population of research was all of the 8th graders of Junior High Schools throughout Tegal regency in the school year of 2014/2015. The sampling technique used was stratified cluster random sampling. The data analysis was conducted using a two-way anava with unbalanced cells at significance level of 5%. The results of research showed: (1) the learning achievement of students treated with PBL PS was equally good to that of those treated with GI PS, that of those treated with PBL PS and GI PS was better than that of those with TPS PS, (2) the learning achievement of students with high reasoning ability was equally good to that of those with medium one, the learning achievements of students with high and medium reasoning ability were better than that of those with low one, (3) in each reasoning ability, the learning achievement of students treated with PBL PS was equally good to that of those treated with GI PS, that of those treated with PBL PS and GI PS was better than that of those with TPS PS, and (4) in each learning model, the learning achievement of students with high reasoning ability was equally good to that of those with medium one, the learning achievements of students with high and medium reasoning ability were better than that of those with low one.Keywords: Scientific PBL (PBL PS), scientific GI (GI PS), scientific TPS (TPS PS) and reasoning ability.